Mia in the mix graphic novel Cupcake Diaries / vol. 2 - Simon, Coco; Glass House Graphics (Clermont, Florida) (2022)
"When Mia arrives at her new school, her goal is to be open to and friendly with everyone, but everyone at Park Street School fits into a clique. When the Popular Girls Club takes an interest in Mia's awesome fashion style and wants to recruit her, Mia must decide between them and her great new Cupcake Club friends. It's like choosing between her divorced mom and dad and her old house and new house. Is it always going to be Mia in the middle, or can she mix it up?"--
Ages 8-12
Grades 4-6